When Innovation Moves at Digital Speed: Strategies and Tactics to Provoke, Sustain, and Defend Innovation in Today's Unsettled Markets - Review (MIT Press, 2018)
Monograph
fulltext
Keywords: Computing and Processing; General Topics for Engineers